Improving the Digital Competency of Learning Guidance Tutors Through the ADDIE-Based Continuing Professional Development (CPD) Program - Finda Vericha Ngenda; Ahmad Suriansyah; Aslamiah Aslamiah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Continuing Professional Development (CPD) is an essential component of educational human resource management aimed at improving tutors' competencies in responding to the demands of twenty-first-century learning. Preliminary observations indicate that tutors teaching at BUNGA Tutoring Center still face limitations in designing digital learning media that are engaging and easily accessible for learners. This condition highlights the need for a structured, simple, and relevant CPD program within the context of non-formal educational human resource management. This study aims to develop a CPD program based on the ADDIE model to enhance tutors' competencies in designing digital learning media using Google Sites. The study employs a research and development (R&D) approach using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research participants comprised 15 tutors teaching at elementary, junior high, and senior high school levels. Data were collected through pre-tests, post-tests, product assessments, response questionnaires, and observations. Data analysis was conducted using descriptive quantitative and qualitative techniques. The results indicate an improvement in tutors' competencies, as evidenced by increased pre-test and post-test scores with a high N-Gain category. The developed digital learning media products were categorized as good to very good, and tutors' responses to the CPD program were classified as highly positive.